2016
DOI: 10.1080/19768354.2016.1194318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kinship on the allopreening among juvenile Bengalese finches

Abstract: Kin-directed affiliative behavior is widespread in social animals and kin selection theory suggests that such behavior increases fitness of the performer and is thus adaptive. Allopreening in birds is an altruistic behavior as it involves cleaning body parts that cannot be cleaned by selfpreening. In this study, we investigated the effects of genetic relatedness on allopreening behavior among juveniles of the Bengalese finch Lonchura striata domestica shortly after the cessation of parental care. Nestlings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Thus, although this behavior has traditionally been interpreted in terms of kin selection in social insects, other forms of selections may take role in its evolvement. In vertebrates, reciprocal altruism is thought to play a larger role (Clutton-Brock, 2009), although kin selection may also have some function (Ju and Lee, 2016).…”
Section: So What Are We Missing?mentioning
confidence: 99%
“…Thus, although this behavior has traditionally been interpreted in terms of kin selection in social insects, other forms of selections may take role in its evolvement. In vertebrates, reciprocal altruism is thought to play a larger role (Clutton-Brock, 2009), although kin selection may also have some function (Ju and Lee, 2016).…”
Section: So What Are We Missing?mentioning
confidence: 99%
“…In the same way, young storks are very aggressive towards a new foreign chick (Redondo et al, 1995). In another study, chicks of Bengalese finches make more allopreening between biological siblings than adopted ones, showing that they can recognize biological siblings and produce affiliative behaviour according relatedness (Ju and Lee, 2016).…”
Section: A C C E P T E D a U T H O R M A N U S C R I P T Smentioning
confidence: 88%
“…Studies in birds have shown that individuals can recognize and preferentially attend to siblings (Nakagawa & Waas, 2004). In a cross-fostering study with juvenile Bengalese finches (Lonchura striata domestica), preening bouts between genetic siblings were longer and more frequent that preening bouts between foster siblings (Ju & Lee, 2016). In house sparrows (Passer domesticus), juveniles preferred to follow siblings (Tóth et al, 2009) over unrelated conspecifics.…”
Section: Discussionmentioning
confidence: 99%